(untitled) - Kobayashi, Kōji (Cambridge, Mass., 1986)
This book, Kobayashi puts forth one of his practical and realizable visions: C&C, or the perfect union of computers and communications. Integrating them has become possible because both now involve the processing of digitalized information through semiconductor circuits. Here he describes a remarkably ambitious C&C project that is unlikely to reach the pay-off point until early in the next century: the automatic interpretation telephone system.
Keywords: Truyền thông số,Digital communications